Preliminary Investigation on Generation of Electricity Using Micro Wind Turbines Placed on A Car - Chaudhary, Yogendra; Bangi, Vijaya; Guduru, Ramesh; Aung, Kendrick; Reddy, Ganesh (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Wind energy is one of the prominent resources for renewable energy and it is traditionally extracted using stationary wind turbines. However, it can also be extracted using mini or micro wind turbines on a moving body, such as an automobile, while cruising at high speeds on freeways. If the electricity is produced using air flowing around the vehicle without affecting aerodynamic performance of the vehicle, it can be used to charge up the battery or power up additional accessories of the vehicle. For the first time, in the present work, a preliminary investigation was carried out to generate electricity by utilizing air flow on a moving car. Initially, a correlation between the car speed and wind velocity was established using an anemometer. Placing a set of two micro wind turbines along with two micro generators on the rear end of the car trunk, the present study investigated the feasibility of generating electricity from these micro wind turbines while evaluating the effect of drag force on the performance of the car through the experimental approach and computational fluid dynamics (CFD) simulations. Both approaches confirmed negligible effect of drag force on the vehicle performance in terms of gas mileage and changes in drag coefficient values. Following these studies, the micro wind turbines were also tested for electricity generation at various cruising speeds of the car ranging from 50 to 80 mph on the freeways. The voltage and power generated always showed an increasing trend with increasing the car speed, however they saturated when a cut off limit was setup with the voltage controllers. A maximum voltage of 3.5 V and a maximum current of 0.8 A were generated by each micro wind turbine when a cut off limit was used along with a load consisting of four LED bulbs in parallel with 3.5 V and 0.2 A rating each. On the other hand, when the tests were repeated without using the cut-off limit, a maximum voltage of 18.91 V and a maximum current of 0.65 A were recorded with a load of six flash bulbs in series (flash bulb rating – 4.8 V and 0.5 A each). These studies clearly demonstrate the flexibility to vary the voltage and current outputs from the micro wind turbines indicating a possibility for utilizing the wind energy on the cars at high speeds.Article History: Received Sept 5th 2016; Received in revised form Dec 6th 2016 ; Accepted January 4th 2017; Available onlineHow to Cite This Article: Bangi, V.K.T., Chaudhary, Y., Guduru, R.K., Aung, K.T and Reddy, G.N. (2017) Preliminary investigation on generation of electricity using micro wind turbines placed on a car. Int. Journal of Renewable Energy Development, 6(1), 75-81.http://dx.doi.org/10.14710/ijred.6.1.75-81